"y''+4y'+4y=0"
initial values:
"y(-1)=4"
"y'(-1)=4"
1-step: Assume a solution will be proportioanl to "e^{\\lambda x}" for some constant "\\lambda" . Substitute "y(x) = e^{\\lambda x}" into the differential equation:
"\\tfrac{d^2 (e^{\\lambda x})}{dx^2} + 4 \\tfrac{d (e^{\\lambda x})}{dx} + 4e^{\\lambda x} = 0"
2-step: Substiute "\\tfrac{d^2 (e^{\\lambda x})}{dx^2} = \\lambda ^2 e^{\\lambda x}" and "\\tfrac{d (e^{\\lambda x})}{dx} = \\lambda e^{\\lambda x}"
"\\lambda^2 e^{\\lambda x} + 4\\lambda e^{\\lambda x} + 4e^{\\lambda x} = 0"
3-step: Factor out "e^{\\lambda x}"
"(\\lambda^2+4\\lambda+4)e^{\\lambda x} = 0"
4-step: Since "e^{\\lambda x} {=}\\mathllap{\/\\,}\t0" for any finite "\\lambda" , the zeros must come from the polynomial "\\lambda^2+4\\lambda+4=0"
5-step: Factor
"(\\lambda + 2)^2 = 0"
6-step: Solve for "\\lambda"
"\\lambda = -2" or "\\lambda = -2"
7-step: The multiplicity of the root "\\lambda = -2" is 2 which gives y1(x) = C1 "e^{-2x}" , y2(x) = C2 "e^{-2x} x" as solutions, where C1 and C2 are arbitrary constants.
The general solution is the sum of the above solutions:
y(x) = y1(x) + y2(x) = C1"e^{-2x}" + C2"e^{-2x}x"
8-step: Solve for the unknown constants using the given initial conditions
Compute "\\tfrac{dy(x)}{dx}:"
"\\tfrac{dy(x)}{dx} = \\tfrac{d }{dx}" (C1"e^{-2x} +" C2"e^{-2x}x" ) = - 2C1"e^{-2x} +" C2"e^{-2x} -" 2C2"e^{-2x} x"
9-step: Substitute y(-1) = 4 into y(x) = C1"e^{-2x} + e^{-2x}x"C2
"e^{2}" C1 - "e^{2}" C2 = 4
10-step: Substitute y'(-1) = 4 into "\\tfrac{dy(x)}{dx} = -2e^{-2x}" C1 + "e^{-2x}" C2 - "2e^{-2x}x" C2
-2C1"e^{2} + 3e^{2}" C2 = 4
11-step: Solve the system:
C1 = "\\tfrac{16}{e^{2}}"
C2 = "\\tfrac{12}{e^{2}}"
Substitute C1 = "\\tfrac{16}{e^{2}}" and C2 = "\\tfrac{12}{e^{2}}" into y(x) = "e^{-2x}" C1 + "e^{-2x}x" C2
Comments
Leave a comment